Behavior of multi-walled carbon nanotubes on the porosity and microstructure of cement-based materials - Nochaiya T. (2017)
The porosity and microstructure of a Portland cement-multi-walled carbon nanotube composite were investigated. Multi-walled carbon nanotubes (CNTs), up to 1 wt.% of cement, synthesized by infusion chemical vapor deposition, and Portland cement type I (PC) were used to produce pastes with a water to cement ratio of 0.5. Mercury intrusion porosimetry (MIP) and scanning electron microscopy (SEM) were used to characterize Portland cement-CNTs systems. MIP analysis of the results indicates that total porosity of the mixes with CNTs was found to decrease with increasing CNTs content. Moreover, an important effect of additional CNTs was a reduction in the number of mesopores, while SEM technique showed dispersion of CNTs between the hydration phases of Portland cement pastes. © 2010 Elsevier B.V. All rights reserved.